2012
DOI: 10.1073/pnas.1120645109
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting platelet-stimulated blood coagulation by inhibition of mitochondrial respiration

Abstract: Platelets are important mediators of blood coagulation that lack nuclei, but contain mitochondria. Although the presence of mitochondria in platelets has long been recognized, platelet mitochondrial function remains largely unaddressed. On the basis of a small amount of literature that suggests platelet mitochondria are functional, we hypothesized that the inhibition of platelet mitochondria disrupts platelet function and platelet-activated blood coagulation. To test this hypothesis, members of the tetrazole, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…Normal activity of blood coagulation requires platelets as a critical factor. Studies have shown that platelets are involved in many biological clotting processes, including detection of vascular lesions, coagulation cascade startup, and activation of other platelets15. Additional studies presented here provided evidence that, in the presence of metformin, platelet prothrombinase activity was markedly impaired.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Normal activity of blood coagulation requires platelets as a critical factor. Studies have shown that platelets are involved in many biological clotting processes, including detection of vascular lesions, coagulation cascade startup, and activation of other platelets15. Additional studies presented here provided evidence that, in the presence of metformin, platelet prothrombinase activity was markedly impaired.…”
Section: Discussionsupporting
confidence: 54%
“…Some indications as to the role mitochondria play in platelet function have been elucidated151617. Early reports primarily examined the role that mitochondria play in meeting the energy demands required for platelet aggregation and granule release16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mackman et al postulate that coagulation is an important component of the inflammatory response and necessary to eliminate the infection 87 . The prevailing view is that coagulation factor production is restricted to three compartments: the liver, where most coagulation factor production takes place; the endothelium, which is characterized, for example, by high levels of von Willebrand Factor (vWF); and the platelets, which, despite being devoid of nuclei, are capable of substantial coagulation factor production 88 . However, there is evidence to refute this simplistic model of coagulation factor synthesis.…”
Section: Commentmentioning
confidence: 99%
“…However, the mechanisms underlying platelet activation-or apoptosis-induced GPIba ectodomain shedding remain obscure. Several studies have shown that mitochondria play an important role in platelet activation [14][15][16][17] and apoptosis [9,13,[18][19][20][21][22]. Although the role of mitochondria in regulating ADAM17 activation has been recently reported [23][24][25], it still remains to be elucidated whether mitochondria play a role in GPIba ectodomain shedding.…”
Section: Introductionmentioning
confidence: 96%